USING ROLE-PLAYING GAMES TO DEVELOP ORAL COMMUNICATION SKILLS IN A FOREIGN LANGUAGE - Hatamova Ruhshona Azimjon qizi,; Ahatova Jasmina Davlatovna,; Z.Sh.Khamuradova, (TADQIQOTLAR, 2026)
Abstract: This article examines the role of role-playing games in enhancing oral communication skills in foreign language learning. It highlights how interactive and situational learning activities help learners improve fluency, accuracy, confidence, and communicative competence. The study shows that role-playing games create realistic communicative  environments  where  students  actively  use  language  for  meaningful interaction.  The  findings  indicate  that  such  activities  reduce  anxiety,  increase motivation, and support spontaneous speech production. Overall, role-playing games are identified as an effective pedagogical tool for developing oral communication skills in foreign language education.